Domestic Violence against Educated Woman: Registered Cases of Kathmandu District - Gyawali, Sindhu (Nepal Journal of Multidisciplinary Research, 2020)
This paper attempts to explore the severity of domestic violence experienced by educated woman of Kathmandu.The views presented in this paper are based on my research about theregistered cases of domestic violence against educated women. I have taken in-depth interviews with 14 women of Kalimati Woman Cell. Here I argue that domestic violence, the most heinous act is even found in educated woman and social acceptance of domestic violence is the primary cause for its prevalence and increase. Moreover, I have taken only the registered cases and it is mostly the educated women who go to women cells to register the cases than the uneducated ones.Educated woman tolerate the pain of domestic violence due to prestige and honour of the family. Education provides knowledge and awareness and enlightens the mind of people. But women are still not awakened and have not been able to discard the perpetrators who have abused them. As violence remains within the home, it remains invisible and accepted as ‘normal’. It is the most shocking truth that,no matter what the educational status of women, women from everywhere face different forms of domestic violence.